Large-Channel Interlaminar Endoscopic Discectomy for Highly Migrated Lumbar Disc Herniation: Effectiveness and Safety - Zheng S; Zhao Q; Hu Z; Li H; Wang B; Zhu Z; Qiu Y; Sun X (Journal of Pain Research)
Shicheng Zheng, Qinghua Zhao, Zongshan Hu, Haibo Li, Bin Wang, Zezhang Zhu, Yong Qiu, Xu Sun Division of Spine Surgery, Department of Orthopedic Surgery, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Xu Sun, Division of Spine Surgery, Department of Orthopedic Surgery, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, People’s Republic of China, Email drsunxu@163.comPurpose: Highly migrated lumbar disc herniation (HM-LDH) presents a significant challenge for surgeons. This study aimed to assess the safety and clinical outcomes of large-channel interlaminar endoscopic discectomy for HM-LDH and compare it to open fenestration discectomy.Patients and Methods: Patients who underwent large-channel interlaminar endoscopic discectomy (group A) or open fenestration discectomy (group B) for HM-LDH between January 2021 and December 2023 were included. Radiological and clinical outcomes were evaluated over at least one year. Operation time, intraoperative blood loss, postoperative drainage, postoperative hospital stay, patient-reported outcomes and complications were compared between groups, independent sample t-tests and Fisher’s exact probability test were performed for two groups.Results: One hundred and thirty-six patients were retrospectively included in this study, with 84 in group A and 52 in group B, respectively. Although similar operative time was observed in group A and group B, group A was detected with significantly less intraoperative blood loss (17.6 ± 6.0 mL vs 101.7 ± 62.0 mL, P = 0.003) and shorter postoperative hospital stay (2.4 ± 0.6 days vs 5.2 ± 2.2 days, P < 0.001). Additionally, postoperative drainage was required in group B (35.9 ± 26.4 mL), but none in group A. Follow-up durations averaged 22.8 ± 4.9 months for group A and 20.2 ± 4.2 months for group B. Both groups achieved a significant improvement in VAS, ODI and EQ-5D scores without significant differences. No case experienced neurological deficits and reoperation after surgery in either group. The overall percentage of patients with good to excellent results according to modified MacNab criteria of group A was 95.2%, versus 92.3% of group B.Conclusion: For the treatment of HM-LDH, large-channel interlaminar endoscopic discectomy is an effective and safe treatment.Keywords: spine endoscopy, open fenestration discectomy, highly migrated disc herniation, clinical effectiveness